2014
DOI: 10.1155/2014/738298
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin Codon 54 Gene Polymorphism and Vulvovaginal Candidiasis: A Systematic Review and Meta-Analysis

Abstract: Mannose-binding lectin (MBL) plays a key role in the human innate immune response. It has been shown that polymorphisms in the MBL2 gene, particularly at codon 54 (variant allele B; wild-type allele designated as A), impact upon host susceptibility to Candida infection. This systematic review and meta-analysis were performed to assess the association between MBL2 codon 54 genotype and vulvovaginal candidiasis (VVC) or recurrent VVC (RVVC). Studies were searched in MEDLINE, SCOPUS, and ISI Web of Science until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
(60 reference statements)
3
33
0
Order By: Relevance
“…Polymorphisms in the MBL2 gene are more frequent in African-Americans and multiple studies have suggested an association between MBL2 genetic variants that result in diminished MBL2 protein levels and preterm birth, and conditions commonly found in preterm pregnancies including chorioamnionitis (Annells et al 2004(Annells et al , 2005Gibson et al 2011;Jaffe et al 2013;Capece et al 2014;Nedovic et al 2014). Our discovery of a nonsense mutations that significantly truncates the MBL2 protein is thus consistent with the notion that loss of this antimicrobial protein increases risk of prematurity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Polymorphisms in the MBL2 gene are more frequent in African-Americans and multiple studies have suggested an association between MBL2 genetic variants that result in diminished MBL2 protein levels and preterm birth, and conditions commonly found in preterm pregnancies including chorioamnionitis (Annells et al 2004(Annells et al , 2005Gibson et al 2011;Jaffe et al 2013;Capece et al 2014;Nedovic et al 2014). Our discovery of a nonsense mutations that significantly truncates the MBL2 protein is thus consistent with the notion that loss of this antimicrobial protein increases risk of prematurity.…”
Section: Discussionsupporting
confidence: 83%
“…; Nedovic et al. ). Our discovery of a nonsense mutations that significantly truncates the MBL2 protein is thus consistent with the notion that loss of this antimicrobial protein increases risk of prematurity.…”
Section: Discussionmentioning
confidence: 97%
“…This study also found higher frequencies of a mutation causing a premature stop codon in the C-type lectin receptor Dectin-1 in women with RVVC, which mediates IL-22 production [48]. Polymorphisms in mannose binding lectin (MBL), a component of innate immunity that triggers complement activation, are also found at higher frequencies in RVVC patients and are associated with leading reduced vaginal MBL levels [49,50]. Overall, these studies support the concept that pathways important in mucosal tolerance that may limit innate responsiveness to a commensal symbiont promote resistance to RVVC.…”
Section: Candida Albicans: the Ubiquitous Fungal Symbiontmentioning
confidence: 89%
“…This is in contrast to vulvovaginal candidiasis, where a recent meta-analysis demonstrated an increased risk in women harboring the MBL2 exon 1 codon 54 (A/B) variant (36). We can only speculate that other PRR (e.g.…”
Section: Discussionmentioning
confidence: 69%